MHC class I chain-like gene A (MICA) and its associations with inflammatory bowel disease and peripheral arthropathy. - Orchard, T; Dhar, A; Simmons, J; Vaughan, R; Welsh, K; Jewell, D (2001)
MHC class I chain gene A (MICA) is a non-classical Class I gene which is expressed on the surface of epithelia without beta 2-microglobulin. The gene is found in the major histocompatibility complex (MHC) in tight linkage disequilibrium with human leucocyte antigen-B (HLA-B). Its precise function is unknown, but it interacts with gamma delta T cells of the intestinal immune system. This region of the MHC has been implicated in inflammatory bowel disease (IBD) pathogenesis by recent association mapping studies and this study was performed to examine the prevalence of MICA gene polymorphisms in IBD, in particular in type 2 peripheral arthropathy (PeA), which also has a strong HLA-B association. An assessment of the prevalence of MICA polymorphisms in IBD was made. Blood from 50 ulcerative colitis (UC) and 50 Crohn's disease controls was taken and MICA status determined using allele-specific PCR for 16 known alleles of MICA. A further 91 UC patients were recruited to confirm the results of this stage, and then the polymorphisms were studied in 52 type 1 and 45 type 2 PeA patients. The MICA status of these groups was compared with 118 blood and organ donor controls with appropriate correction for multiple comparisons. UC overall was associated with possession of MICA*007 in 32% compared to 11% of controls (P(c) = 0.017). This association was confirmed in a second cohort of 91 patients (23% versus 11%, P = 0.02). These were independent of HLA class I status. Type 2 IBD PeA was associated with MICA*008 in 98% compared to 73% of controls (P = 0.0001). MICA*007 is associated with susceptibility to UC in our population and MICA*008 with type 2 IBD PeA. Further work is now required to assess the distribution and expression of MICA throughout the gut in health and disease.